Readiness Assessment of Electronic Health Records Implementation - Ajami, Sima (AVICENA, d.o.o., Sarajevo, 2011)
INTRODUCTION: During the past 20 years, with huge advances in information technology and particularly, in the areas of health, various forms of electronic records have been discussed, designed or implemented. Although making health records automatically has many advantages but unfortunately in some cases, creation of an Electronic Health Record (EHR) system seems to be complicated. E-health (Electronic health) readiness assessment, as a part of the assessment before implementation is considered essential and prior to implementation. Readiness assessment aims to evaluate preparedness of each organizational component. This process can lead to the correct decision making. Therefore, identifying areas and requirements for such an assessment is so essential. Using the results of this assessment can identify deficiencies in the existing electronic health records to plan their strategies. The aim of this study was first; to show the situation of readiness assessment in EHR implementation roadmap, second, to recognize requirements associated with electronic readiness assessment and main areas of EHR readiness assessment. RESULTS AND DISCUSSION: This study reviewed the literature on EHR readiness assessment with the help of library and also searches engines available at Google. For our searches, we employed the following keywords and their combinations: readiness, assessment, implementation, Electronic Health Record (EHR), Information Technology, road map in the searching areas of title, keywords, abstract, and full text. In this study, more than 100 articles and reports were collected and 45 of them were selected based on their relevancy.